Evaluation of Terpene Variability in the Volatile Oils from Zingiber officinale using Chemometrics - Jahiddin, Farah S.A.; Low, Kah H. (Current Analytical Chemistry, 2020)
Background: Ginger oil poses various pharmacological properties corresponding to its terpene composition which depends upon the preparation method along with the sample variety. Objective: This work aims to explore the variability in the derived oil associated with the hydrodistillation settings i.e. sample freshness/dryness, size reduction process, and heating duration using chemometric approaches. Methods: The extraction process was evaluated with a two-level full factorial design where the volatile oils were hydrodistillated and characterized by gas chromatographic-mass spectrometry. The multivariate dataset ascertained was further explored with principal component analysis. Results: According to the outcomes from the design, the yield could be quantitatively improved by using fresh sample, with reduced particle thickness and longer extraction cycle. The clastering patterns from principal component analysis revealed the domination of monoterpenes in the extracts from fresh samples; sesquiterpenes in the grated samples; whereas heating duration demonstrated antagonistic effect between monoterpenes and sesquiterpenes. Conclusion: These findings suggest the importance of experimental conditions in driving the yield and quality of ginger extracts according to the requirement of the industries.
Keywords: principal component analysis